Major changes in the sphingophospholipidome of HDL in non-diabetic patients with metabolic syndrome. (March 2016) - Denimal, Damien; Nguyen, Amandine; Pais de Barros, Jean-Paul; Bouillet, Benjamin; Petit, Jean-Michel; Vergès, Bruno; Duvillard, Laurence
Abstract: Objective: Phospholipids and sphingolipids play a critical role in the protective effects of HDL against atherosclerosis. These properties are impaired in patients with metabolic syndrome, before the development of diabetes. We thus investigated whether HDL from patients with metabolic syndrome but normal fasting glycaemia present abnormalities in their sphingophospholipid profile. Methods: Using liquid chromatography/tandem mass spectrometry, we quantified the different species of the main phospholipids and sphingolipids in the HDL2 and HDL3 from 26 obese patients with metabolic syndrome but normal fasting glycaemia and 50 controls. Results: Phosphatidylcholines, when expressed as the relative amount compared with total phospholipids and sphingolipids, were similar in both HDL2 and HDL3 in the two groups. Lysophosphatidylcholines were 41% (p = 0.0002) and 86% (p < 0.0001) higher in HDL2 and HDL3, respectively, from patients with metabolic syndrome than in those from controls. Phosphatidylinositols were also higher in HDL2 and HDL3 (respectively,  +60 and + 103% (p < 0.0001)). In contrast, both HDL2 and HDL3 from patients with metabolic syndrome showed lower proportions of phosphatidylethanolamine-based plasmalogens (respectively −78 and −73%, p < 0.0001), phosphatidylcholine-based plasmalogens (respectively −44 and −53%, p < 0.0001), d18:1-sphingosine-1-phosphate (respectively −52 and −38%, p < 0.0001) and sphingomyelins (respectively −19% (p < 0.0001) and −24% (p = 0.0006)), than did controls. Moreover, we observed a decrease in C18:2 fatty acid-containing phospholipids and an increase in C20:4 fatty acid-containing phospholipids. Conclusion: The sphingophospholipidome of HDL from normoglycaemic obese patients with metabolic syndrome is profoundly modified, before the dysregulation of glycaemia. Most of the changes observed have pejorative effect in terms of vascular protection. Highlights: In metabolic syndrome without diabetes the HDL2 and HDL3 sphingophospholipidome shows major changes. The proportion of sphingomyelins, plasmalogens and d18:1-sphingosine-1-phosphate is decreased. The proportion of lysophosphatidylcholines and phosphatidylinositols is increased. These changes could contribute to the impaired functionality of HDL in metabolic syndrome. C18:2 fatty acid-containing phospholipids are decreased and C20:4 fatty acid-containing ones are increased.